Research in contemporary society: The role of artificial intelligence in academic research writing - Ugo Chuks Okolie; Thomastina Nkechi Egbon (Qualitative Research of Business and Social Sciences, 2024)
The quality and effectiveness of the academic research writing process could be enhanced by applying artificial intelligence (AI). Using AI algorithms, researchers can easily and quickly generate precise, well-written, high-quality text. The role of AI in academic writing has recently been the topic of discussion. Researchers have paid less attention to the importance of AI in academic research writing in developing countries, even though it is widely used in academic research writing. AI has become a more significant component of academic writing in recent years. Therefore, this study aimed to examine the use of AI in academic research writing. This study's data came from secondary sources, such as books, journals, and websites, that provided relevant information. Moreover, an exploratory research design was employed, and the collected data were analyzed using content analysis. This study showed that AI helps academic writers create excellent content quickly and effectively. AI provides writing assistance, improves grammar, optimizes structure, supports editing, and supports ethical compliance. The study concluded that AI profoundly impacts academic research and writing across various fields. Academic researchers must address the potential disadvantages of using AI in research writing through action and ethical compliance. The study has contributed to a better understanding of the benefits, challenges, and ethical considerations associated with the use of AI in academic research writing. The study recommended, among other measures, that AI be applied transparently and ethically. Researchers are obligated to use AI tools to maintain the authenticity and creativity of their work while refraining from any improper use that might jeopardize academic credibility